Systematic mutational analysis of the LytTR DNA binding domain of Staphylococcus aureus virulence gene transcription factor AgrA. Issue 20 (28th October 2014) - Nicod, Sophie S.; Weinzierl, Robert O. J.; Burchell, Lynn; Escalera-Maurer, Andres; James, Ellen H.; Wigneshweraraj, Sivaramesh
Abstract: Most DNA-binding bacterial transcription factors contact DNA through a recognition α-helix in their DNA-binding domains. An emerging class of DNA-binding transcription factors, predominantly found in pathogenic bacteria interact with the DNA via a relatively novel type of DNA-binding domain, called the LytTR domain, which mainly comprises β strands. Even though the crystal structure of the LytTR domain of the virulence gene transcription factor AgrA from Staphylococcus aureus bound to its cognate DNA sequence is available, the contribution of specific amino acid residues in the LytTR domain of AgrA to transcription activation remains elusive. Here, for the first time, we have systematically investigated the role of amino acid residues in transcription activation in a LytTR domain-containing transcription factor. Our analysis, which involves in vivo and in vitro analyses and molecular dynamics simulations of S. aureus AgrA identifies a highly conserved tyrosine residue, Y229, as a major amino acid determinant for maximal activation of transcription by AgrA and provides novel insights into structure–function relationships in S. aureus AgrA.